2006
DOI: 10.1080/00986440500352014
|View full text |Cite
|
Sign up to set email alerts
|

Cloud Point and Dye Solubilization Studies of Amphiphilic Drug Solutions: The Effect of Electrolytes and Nonelectrolytes

Abstract: The effect of electrolytes and nonelectrolytes on the micellar behavior of amitriptyline (AMT), an amphiphilic drug, has been investigated using cloud point (CP) and dye solubilization techniques. The critical micelle concentration (cmc) of AMT determined by the Wilhelmy plate method was about 40 mM in the presence of 10 mM sodium phosphate, and it reduced to about 20 mM in the presence of 500 mM sodium phosphate. Interestingly, the CP phenomenon was observed even below the cmc in cationic AMT solutions. Incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 30 publications
1
10
0
Order By: Relevance
“…In the presence of glucose/fructose, the solubility, as well as the micellar size of TX-100, was reduced. 25,26 Maclay found the variation of the CP of TX-100 as a function of polyols concentration to be reduced with the upsurge of polyols concentration. 27 In our current study, we also observed a similar result; that is, the CP values of TX-100 were found to decrease with the augmentation of the glucose/fructose concentration (Figure 2).…”
Section: Resultsmentioning
confidence: 99%
“…In the presence of glucose/fructose, the solubility, as well as the micellar size of TX-100, was reduced. 25,26 Maclay found the variation of the CP of TX-100 as a function of polyols concentration to be reduced with the upsurge of polyols concentration. 27 In our current study, we also observed a similar result; that is, the CP values of TX-100 were found to decrease with the augmentation of the glucose/fructose concentration (Figure 2).…”
Section: Resultsmentioning
confidence: 99%
“…Polyols may reduce the solubility of TX-100 and reduce the micelle size. 31,32 Lowering of CP values of the TX-100 + PEG-400 mixture by polyols is a linear function of the polyol concentration reported by Maclay. 33 From Table 3 and Figure S1 (Supporting Information), it is found that the addition of polyols to the PEG-400 + TX-100 mixture reduces the CP of the mixture to a small extent with the exception.…”
Section: Resultsmentioning
confidence: 83%
“…A great deal of research has been conducted on CP determination by visual methods in the past decade. ,,,,, Recent work on the clouding phenomenon and other related parameters of drugs ceftriaxone sodium trihydrate and the phenothiazine family reported in the literature have also used the same method for CP determination. It is known that the clouding behavior of drugs depends on the solvation or desolvation equilibrium existence. The presence of additives in water and in EtOH–WR mixed media can change such an equilibrium, and as a result, the CP of the drug solutions may vary significantly.…”
Section: Resultsmentioning
confidence: 99%
“…Amphiphilic molecules consist of hydrophobic tails and hydrophilic headgroups. They self-assemble to form well-defined aggregates by way of hydrophobic interaction within the nonpolar hydrocarbon part, and the electrostatic interaction of the polar or ionic headgroups and the aggregates thereby formed are called micelles. , The self-assembly in these associated colloids is a natural and spontaneous process which comes into play as a result of noncovalent interactions such as van der Waals, electrostatic, hydrogen bonding, and hydrophilic/hydrophobic interactions …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation